Specificity of hammerhead ribozyme cleavage. - Hertel, K J (1996)
To be effective in gene inactivation, the hammerhead ribozyme must cleave a complementary RNA target without deleterious effects from cleaving non-target RNAs that contain mismatches and shorter stretches of complementarity. The specificity of hammerhead cleavage was evaluated using HH16, a well-characterized ribozyme designed to cleave a target of 17 residues. Under standard reaction conditions, HH16 is unable to discriminate between its full-length substrate and 3'-truncated substrates, even when six fewer base pairs are formed between HH16 and the substrate. This striking lack of specificity arises because all the substrates bind to the ribozyme with sufficient affinity so that cleavage occurs before their affinity differences are manifested. In contrast, HH16 does exhibit high specificity towards certain 3'-truncated versions of altered substrates that either also contain a single base mismatch or are shortened at the 5' end. In addition, the specificity of HH16 is improved in the presence of p7 nucleocapsid protein from human immunodeficiency virus (HIV)-1, which accelerates the association and dissociation of RNA helices. These results support the view that the hammerhead has an intrinsic ability to discriminate against incorrect bases, but emphasizes that the high specificity is only observed in a certain range of helix lengths.